2015
DOI: 10.5455/msm.2015.27.276-279
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation and the Outcome of Therapy in a Cohort of Patients with Methadone Toxicity in Iran

Abstract: Background:Agonist maintenance therapy with methadone is amongst the preferred remedies for treating opioid dependence and is increasingly supported by the regional governments in this part of the world. In this study we have investigated the clinical manifestations and factors affecting the outcome of therapy in patients with methadone poisoning in a Middle-Eastern (Iranian) referral tertiary care University hospital.Methods:In this prospective and descriptive-analytic study which was done in a tertiary care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
2
13
1
Order By: Relevance
“… 78 81 There are numerous studies conducted on MET overdose. 82 – 84 In a pathological examination of the livers of individuals who had died of MET overdose, positive hepatic pathological findings were observed in 43.9% of them, including hepatocyte degeneration in 2.4%, hepatic steatosis in 9.8%, hepatocyte necrosis in 24.4%, and more than one pathological finding in 7.3%. 84 The study by Darke et al on the individuals who had died of MET overdose indicated a hepatic pathology prevalence rate equal to 80.7%.…”
Section: Discussionmentioning
confidence: 99%
“… 78 81 There are numerous studies conducted on MET overdose. 82 – 84 In a pathological examination of the livers of individuals who had died of MET overdose, positive hepatic pathological findings were observed in 43.9% of them, including hepatocyte degeneration in 2.4%, hepatic steatosis in 9.8%, hepatocyte necrosis in 24.4%, and more than one pathological finding in 7.3%. 84 The study by Darke et al on the individuals who had died of MET overdose indicated a hepatic pathology prevalence rate equal to 80.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Methadone toxicity outcomes can depend on us factors like age, gender, history of suicide attempts and psychological disorders, and the time interval between consumption of the drug and obtaining medical care (Eizadi-Mood et al 2015). All of the aforementioned cases, except Tóth and Varga (2009) involved young males; also, as described in the original articles, men more frequently present with acute methadone toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In two later studies, opiate toxicity was found to be the most common cause of rhabdomyolysis (Talaie et al 2007, 2008). In addition, rhabdomyolysis can be induced by methadone abuse (Criner et al 2002; Iranmanesh 2015; Gramenz et al 2010; Nanji and Douglas Filipenko 1983; Aghabiklooei et al 2014; Eizadi-Mood et al 2015). …”
Section: How Methadone Affects the Kidneymentioning
confidence: 99%
“…Despite its efficacy, there are no comprehensive care facilities for the people who are still under treatment. [123456]…”
Section: Introductionmentioning
confidence: 99%
“…[2] Furthermore, the epidemiology of deaths from opioid toxicity in a poisoning referral center showed that the majority of deaths have been observed most in patients with methadone poisoning. [3] Pulmonary edema is a mortal complication for acute methadone overdose which causes mortality in many patients. Considering the fact that methadone toxicity is common in our society, we evaluated the prevalence of pulmonary edema in the deceased cases with methadone poisoning and considered its possible relationship with different variables.…”
Section: Introductionmentioning
confidence: 99%